Balancing Competition and Cooperation: The State's New Power in Crisis Management - Anke Hassel; Susanne Lütz (London School of Economics and Political Science (LSE), European Institute, 2012)
In the aftermath of the financial crisis, governments in the western world resumed policy instruments from the immediate post-war periods mixed economies. These instruments had all been abandoned in the liberalizing market economies of the last decades. How do we interpret these developments in the state's role in modern economies? Will we witness the return of the interventionist state or are these rather short-term measures rescuing globalized and liberal market economies? By focusing on the initial phase of crisis management between 2008 and 2010 we analyse the three most important policy tools used of the financial crisis: state ownership of banks, fiscal stimuli and the regulation of financial markets. We observe a new capacity of the nation-state to intervene, going beyond mere firefighting, but also falling short of the classic interventionist state. Under the conditions of global markets, state intervention is shaped by the logic of competition for protecting national industries and the logic of cooperation necessary to come to international agreements. For the future, we expect states will retain their newly found powers to protect national business in the global economy.
Keywords: 330